2022
DOI: 10.3389/fcell.2021.802509
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Regulate NLRP3 Inflammasome in Diseases

Abstract: Emerging evidence has suggested the unique and critical role of exosomes as signal molecules vector in various diseases. Numerous researchers have been trying to identify how these exosomes function in immune progression, as this could promote their use as biomarkers for the disease process and potential promising diagnostic tools. NOD-like receptor (NLR) family, pyrin domain containing 3 (NLRP3), a tripartite protein, contains three functional domains a central nucleotide-binding and oligomerization domain (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 175 publications
0
8
0
Order By: Relevance
“…Research has demonstrated that exosomes/microvesicles from periodontal ligament stem cells of MS patients can inhibit NLRP3 inflammasome activation and attenuate the severity of EAE (Soundara Rajan et al, 2017 ). In detail, the effects of exosomes on NLRP3 inflammasome activation depend on the origin of exosomes, including inhibition (from plasma, mesenchymal stem cells, and macrophages) and promotion (from cancer cells) (Li et al, 2021 ). For example, Yan et al ( 2020 ) reported that exosomes derived from human umbilical cord mesenchymal stem cells could inhibit NLRP3 inflammasome activation by releasing circular RNA homeodomain-interacting protein kinase 3 (circHIPK3).…”
Section: Nlrp3 Inflammasome In the Pathogenesis/pathophysiology Of Msmentioning
confidence: 99%
“…Research has demonstrated that exosomes/microvesicles from periodontal ligament stem cells of MS patients can inhibit NLRP3 inflammasome activation and attenuate the severity of EAE (Soundara Rajan et al, 2017 ). In detail, the effects of exosomes on NLRP3 inflammasome activation depend on the origin of exosomes, including inhibition (from plasma, mesenchymal stem cells, and macrophages) and promotion (from cancer cells) (Li et al, 2021 ). For example, Yan et al ( 2020 ) reported that exosomes derived from human umbilical cord mesenchymal stem cells could inhibit NLRP3 inflammasome activation by releasing circular RNA homeodomain-interacting protein kinase 3 (circHIPK3).…”
Section: Nlrp3 Inflammasome In the Pathogenesis/pathophysiology Of Msmentioning
confidence: 99%
“…The NLRP3 inflammasome has been identified as a mediator in a wide variety of diseases and as a potential novel therapeutic target. Since its role in the progression of atherosclerosis, heart failure, glomerulonephritis and several infectious diseases [25][26][27][28][29] has been acknowledged, it would be useful to highlight the most fundamental stages of NLRP3 activation. It resides in the cytoplasm and acts as an immune sensor to a plethora of stimuli, producing IL-1b and IL-18 and initiating the immune response.…”
Section: Mechanisms Of Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…Their application extends from HCC diagnosis, staging and tumor grading to guiding therapeutic management. Several studies [9] considering the NLRP3 as a biomarker in several malignancies have begun to accumulate [29]. The reduced expression of NLRP3 in colorectal cancer (CRC) tissue holds a positive predictive value [93].…”
Section: The Nlrp3 As Biomarkermentioning
confidence: 99%
“…Emerging evidence has revealed the relationship between exosomes and the NLRP3 inflammasome [ 61 , 62 , 63 , 64 ]. Recent studies have shown that exosomes can influence the course of NLRP3 inflammasome-associated diseases by secreting different substances that affect key molecules in the canonical pathway [ 61 , 62 ].…”
Section: The Nlrp3 Inflammasome and Related Pathwaysmentioning
confidence: 99%